THE ROLE OF TECHNOLOGY AND INNOVATION IN DESERTIFICATION MITIGATION (World Bulletin of Social Sciences, 2023)
This scientific article aims to provide a comprehensive analysis of the role of technology and innovation in mitigating desertification. Desertification, a significant environmental challenge, poses serious threats to ecosystems, economies, and human well-being worldwide. To combat this issue, technological advancements and innovative approaches are increasingly being utilized. This article explores the key concepts, examines relevant literature, outlines the methodology used in the study, presents the results, engages in a thorough discussion, and concludes with the potential impact of technology and innovation in desertification mitigation. The findings emphasize the importance of leveraging technology and innovation to address desertification and ensure sustainable development
Keywords: Desertification; technology; innovation